Biopolymeric nanoparticles based effective delivery of bioactive compounds toward the sustainable development of anticancerous therapeutics - Pathak, Neelam; Singh, Pankaj; Singh, Pradeep Kumar; Sharma, Swati; Singh, Rajat Pratap; Gupta, Anmol; Mishra, Richa; Mishra, Vivek Kumar; Tripathi, Manikant (Frontiers in Nutrition, 2022)
Nowadays, effective cancer therapy is a global concern, and recent advances in nanomedicine are crucial. Cancer is one of the major fatal diseases, and a leading cause of death globally. Nanotechnology provides rapidly evolving delivery systems in science for treating diseases in a site-specific manner using natural bioactive compounds, which are gaining widespread attention. Nanotechnology combined with bioactives is a very appealing and relatively new area in cancer treatment. Natural bioactive compounds have the potential to be employed as a chemotherapeutic agent in the treatment of cancer, in addition to their nutritional benefits. Alginate, pullulan, cellulose, polylactic acid, chitosan, and other biopolymers have been effectively used in the delivery of therapeutics to a specific site. Because of their biodegradability, biopolymeric nanoparticles (BNPs) have gotten received a lot of attention in the development of new anticancer drug delivery systems. Biopolymer-based nanoparticles systems with sizes ranging from 1 to 1000 nm can be made in a variety of ways. These systems have developed as a cost-effective and environmentally friendly solution to boost bioavailability, chemical stability, and biological effectstreatment efficacy. Effective drug delivery systems with improved bioavailability, increased selectivity, and lower toxicity are needed. Recent research findings and current knowledge on the use of BNPs in the administration of bioactive chemicals in cancer therapy are summarized in this review.